2021
DOI: 10.3389/fspas.2021.651445
|View full text |Cite
|
Sign up to set email alerts
|

Ionosphere Influenced From Lower-Lying Atmospheric Regions

Abstract: The ionosphere represents part of the upper atmosphere. Its variability is observed on a wide-scale temporal range from minutes, or even shorter, up to scales of the solar cycle and secular variations of solar energy input. Ionosphere behavior is predominantly determined by solar and geomagnetic forcing. However, the lower-lying atmospheric regions can contribute significantly to the resulting energy budget. The energy transfer between distant atmospheric parts happens due to atmospheric waves that propagate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 236 publications
(244 reference statements)
0
9
0
Order By: Relevance
“…As mentioned by Koucká Knížová et al. (2021), the ionospheric variability can be observed at a wide‐scale temporal range that varies from minutes, or even shorter time scales, up to scales of the solar cycle and the secular variations of solar energy input. Although the general behavior of the ionosphere can be determined predominantly by the solar and geomagnetic forcings, the propagation of the lower atmospheric waves up to the ionosphere can contribute significantly to this variability.…”
Section: Introductionmentioning
confidence: 90%
“…As mentioned by Koucká Knížová et al. (2021), the ionospheric variability can be observed at a wide‐scale temporal range that varies from minutes, or even shorter time scales, up to scales of the solar cycle and the secular variations of solar energy input. Although the general behavior of the ionosphere can be determined predominantly by the solar and geomagnetic forcings, the propagation of the lower atmospheric waves up to the ionosphere can contribute significantly to this variability.…”
Section: Introductionmentioning
confidence: 90%
“…The vertically propagating atmospheric waves have an important role in the coupling of the atmosphere-ionosphere system through wave saturation-dissipation processes since they carry energy and momentum, changing the background neutral wind and temperature (Vadas and Fritts, 2006;Yiğit and Medvedev, 2010) and consequently affecting the ionosphere (Vadas and Liu, 2009). As mentioned by Koucká Knížová et al (2021), the ionospheric variability can be observed at a wide-scale temporal range that varies from minutes, or even shorter time scales, up to scales of the solar cycle and the secular variations of solar energy input. Although the general behavior of the ionosphere can be determined predominantly by the solar and geomagnetic forcings, the propagation of the lower atmospheric waves up to the ionosphere can contribute significantly to this variability.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that explosive events can generate acoustic‐gravity waves (AGWs) that propagate, by virtue of the atmosphere's density profile, to thermospheric heights and influence the ionosphere in a way detectable by dual frequency Global Navigation Satellite Systems (GNSS) (Calais et al., 1998; Cheng & Huang, 1992; Hines, 1960; C. Y. Huang et al., 2019; Klobuchar, 1985; Komjathy et al., 2012; Koucká Knížová et al., 2021). Kanamori et al.…”
Section: Introductionmentioning
confidence: 99%